Prospects for the Study and Improvement of Abiotic Stress Tolerance in Date Palms in the Post-genomics Era - Hazzouri, Khaled Michel; Flowers, Jonathan M.; Nelson, David; Lemansour, Alain; Masmoudi, Khaled; Amiri, Khaled M. A. (Frontiers in Plant Science, 2020)
Date palm (Phoenix dactylifera L.) is a socio-economically important crop in the Middle East and North Africa and a major contributor to food security in arid regions of the world. P. dactylifera is both drought and salt tolerant, but recent water shortages and increases in groundwater and soil salinity have threatened the continued productivity of the crop. Recent studies of date palm have begun to elucidate the physiological mechanisms of abiotic stress tolerance and the genes and biochemical pathways that control the response to these stresses. Here we review recent studies on tolerance of date palm to salinity and drought stress, the role of the soil and root microbiomes in abiotic stress tolerance, and highlight recent findings of omic-type studies. We present a perspective on future research of abiotic stress in date palm that includes improving existing genome resources, application of genetic mapping to determine the genetic basis of variation in tolerances among cultivars, and adoption of gene-editing technologies to the study of abiotic stress in date palms. Development of necessary resources and application of the proposed methods will provide a foundation for future breeders and genetic engineers aiming to develop more stress-tolerant cultivars of date palm.